Meningkatkan Kemampuan Pemecahan Masalah Matematis Siswa Melalui Pendekatan Pembelajaran Kontekstual - Rahayu, Diar Veni (Department of Mathematics Education Program IPI Garut, 2012)
This study was intended to know students’ achievement and ability development in mathematical problem solving through contextual learning. This study was conducted in experimental method comparing the mathematical problem solving ability of students that were taught through contextual approach and students that were taught by conventional learning. This research design used pretest-posttest control group design. The population of this study was all students of grade VIII at a school with 80 students from two classes as sample subject. The experimental group was taught using contextual learning and control group was taught using conventional approach. The instrument which was used in this study is mathematical problem-solving ability test and student affective scale based on Likert scale. From this study, it can be concluded that: 1) the mathematical problem-solving ability of students that were taught through contextual approach is better than students that were taught using conventional approach; 2) the development of mathematical problem-solving ability of students that were taught through contextual approach is better than student that were taught using conventional approach; 3) the students showed positive affective in contextual learning.